Cooperativismo no setor cafeeiro no estado do Espírito Santo, 1950 - 1970 - Fassarella, Roberto Amadeu (2020)
The approach of a theme about the cooperativism of a economic sector, such as coffee, is to search knowledge about the spirit and ideals of the human being in the search for social and economic cooperation. It consists in finding in a human collective, th